Advances in intelligent Web mastering - 3 proceedings of the 7th Atlantic Web Intelligence Conference, AWIC 2011, Fribourg, Switzerland, January, 2011 - Mugellini, Elena (Advances in intelligent and soft computing, 2011)
The Atlantic Web Intelligence Conference brings together scientists, engineers, computer users, and students to exchange and share their experiences, new ideas, and research results about all aspects (theory, applications and tools) of intelligent methods applied to Web based systems, and to discuss the practical challenges encountered and the solutions adopted. Previous AWIC events were held in Spain ? 2003, Mexico ? 2004, Poland ? 2005, Israel ? 2006, France ? 2007 and Czech Rep. ? 2009. The present 7th Atlantic Web Intelligence Conference (AWIC?2011) was held during January 26-28, 2011, at the University of Applied Sciences of Fribourg, Switzerland. AWIC2011 is organized by the Multimedia Information System Group (MISG), Institute of the Technologies of Information and Communication (iTIC) of the University of Applied Sciences of Fribourg.